Should 'Responsibility' be written on the tin?: An exploration of CSR at XXXX - Gibson, Elizabeth Sarah (2008)
The purpose of this report is to explore if and how a company known as XXXX could benefit from implementing a CSR policy into their business. Data was collected through a series of interviews and visits to XXXX and analysed in the light of the CSR literature. Strategic CSR can deliver business and societal benefits and the possibilities of this application to XXXX was explored. Through carefully examining the options available it is recommended that XXXX would benefit from exploring further the areas of ethical consumerism and strategic philanthropy. It is also recommended that XXXX examine communication routes for CSR in the first instance among employees - ensuring awareness of current initiatives and recognition of individual entrepreneurialism but also explore further possibilities of communicating XXXX's environmental commitment on the side of the tins. Finally, it was recommended that XXXX implement a simple, concise organisational mission which captures the value of the environment to XXXX.